Energy generation from palm oil mill effluent: A life cycle assessment of two biogas technologies. (15th January 2020) - Sharvini, Siva Raman; Noor, Zainura Zainon; Chong, Chun Shiong; Stringer, Lindsay C; Glew, David
Abstract: This study conducted a life cycle assessment of palm oil mill effluent (POME) based energy generation using the CML 2001 method and Gabi 8 software, focusing on two POME treatment technologies: the covered lagoon bio-digester (CLB) and the continuous stirred tank reactor (CSTR). The analysis determined the respective environmental impacts of the technologies, both of which are currently in use in Malaysia. The global warming potential (GWP) and acidification potential (AP) for CSTR were −4.48 kg CO2 eq/kWh and −2.21 kg SO2 eq/kWh respectively, while for CLB the values were −4.09 kg CO2 eq/kWh and −0.15 kg SO2 eq/kWh. Both technologies produced a negative result, which equates to a net environmental benefit. However, both systems had a negative impact in terms of eutrophication potential (EP). The CSTR nevertheless achieved a better EP result of 0.048 kg PO 4 3 − eq/kWh than the CLB with 0.054 kg PO 4 3 − eq/kWh. A sensitivity analysis was carried out in order to find a way to overcome the impacts of EP. The findings provide useful data to guide decision-makers in the sustainable management of POME, in Malaysia and globally where similar technologies are in use. Graphical abstract: Image 10972 Highlights: Life cycle assessment evaluates two systems to treat palm oil mill effluent. The closed tank captures 4% more carbon dioxide. The closed tank captures 88% more sulphur dioxide. The closed lagoon emits 6% more phosphate. Small increases in sludge for composting result in phosphate emissions below zero.